OPTIMASI PROPORSI CAMPURAN POLIVINIL PIROLIDON DAN AVICEL PH 101 DALAM FORMULASI TABLET ASAM MEFENAMAT SECARA SIMPLEX LATTICE DESIGN - Puspitasari, Dian; Kuncahyo, Ilham (Jurnal Farmasi (Journal of Pharmacy), 2017)
Mefenamic acid is used as an analgesic and non-steroidal anti-inflammatory drugs. The problem that often occurs in the process of compressing is that mefenamic acid tends to stick on the surface of punch and die-compressing machine, so that it often experiences sticking and within a sustainable manner can cause capping process. The other problems of Mefenamic acid are hydrophobic and having low solubility, so that the dissolution becomes a problem. The combination of Avicel PH101 and PVP is expected to fix the problems, so that well-qualified Mefenamic acid tablets can be obtained. This study was aimed at obtaining the optimum formula of mixed Avicel PH101 and PVP in the manufacture of mefenamic acid tablets by wet granulation, based on the method of simplex lattice design (SLD) with two components, namely: Avicel PH101 (A) and PVP (B). Three formulas of mefenamic acid tablets (F1 (100% A), F2 (50% A: 50% B), F3 (100% B)) are made by wet granulation. The granules are tested for the fluidity, compactibility and dissolution. The result is to obtain SLD equation. The equation is used to determine the optimum formula which is the formula with the total response of the most optimal physical properties of granules. The result of the experiment shows that optimum formula was obtained from Avicel PH 101 30% - PVP 70% mixture at granules’ physical properties, and the obtained tablets of Mefenamic acid fulfills tablet physical property test.